Neural mechanisms of perceptual decision-making in the fruit fly - Wong, LHT (2021)
A mobile organism is faced with the challenge of having to decide, moment by moment, its next course of action. Despite extensive efforts in mapping decision-making circuits across many species, the current understanding of neural mechanisms underlying the decision process remains scarce. Fruit flies can perform an odour discrimination task with difficulty-dependent reaction times and choice accuracies, in a framework well-described by a process of evidence accumulation to bound. A subset of third-order olfactory neurons, the αβ core Kenyon cells (αβc KCs), appears to act as a temporal integrator of sensory information, encoding the amount of summed evidence in their subthreshold voltage. However, explicit demonstration of a causal role of these neurons is lacking.